An update on the cutaneous manifestations of coeliac disease and non-coeliac gluten sensitivity. (3rd December 2018) - Graziano, Mario; Rossi, Mauro
Abstract: Introduction: Coeliac disease is a gluten-induced immune-mediated enteropathy, characterised by the expression of specific genotypes and the production of autoantibodies. The inflammatory process specifically targets the intestinal mucosa, but gastrointestinal and extraintestinal signs and symptoms can also be present. Non-coeliac gluten sensitivity (NCGS) can be diagnosed in individuals who have intestinal and/or extraintestinal symptoms related to the ingestion of gluten, but do not have autoantibodies and do not suffer from lesions in the duodenal mucosa. Among the extraintestinal manifestations, cutaneous manifestations are the most common for both diseases.Purpose: We conducted this review to illustrate the common and uncommon features underlying the association of coeliac disease and NCGS with cutaneous manifestations related to gluten ingestion.Areas covered : The roles of innate and adaptive immunity in the cutaneous appearance of gluten sensitivity will be discussed.